Association of Prenatal Acetaminophen Exposure Measured in Meconium With Adverse Birth Outcomes in a Canadian Birth Cohort - Baker, Brennan H.; Burris, Heather H.; Bloomquist, Tessa R.; Boivin, Amélie; Gillet, Virginie; Larouche, Annie; Takser, Larissa; Bellenger, Jean-Philippe; Pasquier, Jean-Charles; Baccarelli, Andrea A. (Frontiers in Pediatrics, 2022)
Background The small number of studies examining the association of prenatal acetaminophen with birth outcomes have all relied on maternal self-report. It remains unknown whether prenatal acetaminophen exposure measured in a biological specimen is associated with birth outcomes. Objectives To investigate the association of acetaminophen measured in meconium with birthweight, gestational age, preterm birth, size for gestational age, gestational diabetes, preeclampsia, and high blood pressure. Methods This birth cohort from Sherbrooke, Québec, Canada, included 773 live births. Mothers with no thyroid disease enrolled at their first prenatal care visit or delivery. Acetaminophen was measured in meconium for 393 children at delivery. We tested associations of prenatal acetaminophen with birthweight, preterm birth, gestational age, small and large for gestational age, gestational diabetes, preeclampsia, and high blood pressure. We imputed missing data via multiple imputation and used inverse probability weighting to account for confounding and selection bias. Results Acetaminophen was detected in 222 meconium samples (56.5%). Prenatal acetaminophen exposure was associated with decreased birthweight by 136 grams (β = -136; 95%CI [-229, -43]), 20% increased weekly hazard of delivery (hazard ratio = 1.20; 95%CI [1.00, 1.43]), and over 60% decreased odds of being born large for gestational age (odds ratio = 0.38; 95%CI [0.20, 0.75]). Prenatal acetaminophen was not associated with small for gestational age, preterm birth, or any pregnancy complications. Conclusions Prenatal acetaminophen was associated with adverse birth outcomes. Although unobserved confounding and confounding by indication are possible, these results warrant further investigation into adverse perinatal effects of prenatal acetaminophen exposure.